(untitled) - Cole, Robert E. (Berkeley, 1971)
Examines the current state of Japanese industry in terms of the opportunities, wages, and benefits available to the blue collar worker and assesses his burgeoning strength as a social and economic force.
Keywords: Giai cấp công nhân,Working class; Nhật Bản,Japan